Analisis Faktor-faktor yang Mempengaruhi Pertumbuhan Industri Perikanan di Indonesia - Arsandi, Sanda Aditiya; Afriyanto, Alan; Kumalasari, Vita (Nekton, 2022)
Indonesia, with one of the highest marine biodiversity in the world, has great fishery potential. This research is quantitative research that desires in knowing the factors that influence the growth of the fishing industry in Indonesia. Industrial growth is measured through the parameters of aquaculture and capture fisheries products. To find the causal factors, correlation tests were conducted on several variables representing internal factors (number of fleets and number of aquaculture households), environment (aquaculture area), economic indicators (consumer price index and inflation), government policies (human development index), population (population density), and law (risk of the population being exposed to criminal acts). The test was carried out using correlation analysis on 2014-2016 data in 34 provinces. The result is that internal and environmental factors have a significant positive effect on the fishing industry. On the other hand, economic factors have no significant effect. Meanwhile, partially HDI has a significant negative effect on capture fisheries products, while population density and the risk of the population being exposed to criminal acts have a significant negative effect on aquaculture results.